OUTPLACEMENT: THE CHALLENGE OF A REALITY IN THE MEXICAN ORGANIZATIONS - Gracia, Tirso Javier Hernández; Gracia, José Francisco Hernández; Sánchez, Ismael Acevedo; Trejo, Alfredo Castillo; Sevilla, Juan Alberto Carranza (European Scientific Journal, ESJ, 2015)
Since companies are the bases of the economy in Mexico, there is an increased interest on the part of the government to boost their growth through various programs, but the increased international competition, mergers, acquisitions and recurring economic crises, give rise to a social and economic phenomenon that is repeated on a daily basis: "unemployment". To offset this problem, it is necessary to implement Outplacement programs that Mexican companies can follow internally and a solid strategy for Corporate Social Responsibility (CSR), which would be designed to restrain the periods of work cutback and minimize the psychological and social impact on those affected. This article discusses the importance of challenging a reality related to Outplacement for Mexican companies, the importance of this phenomenon as part of CSR and some ideas for profit and steps to implement a program.